Nutrition economic evaluation of a probiotic in the prevention of antibiotic-associated diarrhea - Lenoir-Wijnkoop, Irene; Nuijten, Mark J.; Craig, Joyce; Butler, Christopher C. (Frontiers in Pharmacology, 2014)
Introduction Antibiotic associated diarrhea (AAD) is common and frequently more severe in hospitalised elderly adults. It can lead to increased use of healthcare resources. We estimated the cost-effectiveness of a fermented milk with probiotic in preventing AAD and in particular Clostridium difficile associated diarrhea. Methods Clinical effectiveness data and cost information were incorporated in a model to estimate the cost impact of administering a fermented milk containing the probiotic Lactobacillus paracasei ssp paracasei CNCM I-1518 in a hospital setting. Preventing AAD by the consumption of the probiotic was compared to no preventive strategy. Results The probiotic intervention to prevent AAD generated estimated mean cost savings of £339 per hospitalised patient over the age of 65 years and treated with antibiotics, compared to no preventive probiotic. Estimated cost savings were sensitive to variation in the incidence of AAD, and to the proportion of patients who develop non-severe/severe AAD. However, probiotics remained cost saving in all sensitivity analyses. Conclusion Use of the fermented dairy drink containing the probiotic L.paracasei CNCM I-1518 to prevent AAD in older hospitalised patients treated with antibiotics could lead to substantial cost savings.